Pengaruh Kinerja Account Representative, Self Assesment System Dan Kepercayaan Wajib Pajak Terhadap Kepatuhan Sukarela Wajib Pajak Orang Pribadi Pada KPP Pratama Jakarta Kelapa Gading Tahun 2020 - Fatmawati, Fatmawati; Bieattant, Licke (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
The purpose of this study was to analyze the effect of the performance of account representatives, self-assessment system and taxpayer trust on the voluntary compliance of individual taxpayers at the Primary Tax Office of Kelapa Gading, Jakarta. This study used quantitative methods with data collection techniques in the form of a questionnaire technique. The method used in the sample selection is accidental sampling and Slovin’s formula with a margin of error of 5% which produced 400 respondents out of 80,162 registered individual taxpayers. Data were analyzed using multiple linear regression analysis with the help of SPSS 26 for Windows. The results of the t test prove that the performance of account representatives, self-assessment system and taxpayer trust partially has a positive and significant effect on voluntary compliance of individual taxpayers. The results of the F test prove that account representative performance, self-assessment system and taxpayer trust simultaneously have a positive and significant effect on voluntary compliance of individual taxpayers. The results of the R Square research indicate that the account representative performance, self-assessment system and the taxpayer trust affect the voluntary compliance of individual taxpayers at the Primary Tax Office of Kelapa Gading, Jakarta by 65.1%, while the remaining 34.9% is influenced by the other variables outside this study.